Materiales didácticos en el área de matemática para el proceso enseñanza aprendizaje de niños con trastorno del espectro autista - González Sierra, Allison Denisse (2025)
The current study, titled Didactic Materials in the Mathematics Learning Process for Children with Autism Spectrum Disorder (ASD), analyzes the challenges faced by inclusive education for these students. It evaluates how educational resources can aid in understanding mathematical concepts and their impact on socialization and independence in children with ASD. The research is conducted in a school in Guayaquil, where difficulties in adapting educational resources and the need to improve teacher training in inclusive practices are identified, a qualitative method is used applying observation techniques and questionnaires directed at teachers and families. Findings indicate that the use of personalized educational resources facilitates the comprehension of mathematical concepts and student participation in the classroom; a lack of diversity and updates in these resources is observed. To address this issue, a teacher training program is proposed, including the design, adaptation, and implementation of specific educational resources for children with ASD. The conclusions highlight the importance of continuous teacher training and the need to develop appropriate pedagogical strategies that promote more effective inclusive education. A monitoring and evaluation system is recommended to ensure the improvement of educational resources and their impact on learning.